Alpha Defensin-1 Biomarker Outperforms Culture in Diagnosing Breast Implant-Related Infection: Results from a Multicenter Prospective Study. Issue 4 (5th December 2022) - Basta, Marten N.; White-Dzuro, Colin G.; Rao, Vinay; Liu, Paul Y.; Kwan, Daniel; Breuing, Karl H.; Sullivan, Rachel; Mermel, Leonard A.; Drolet, Brian C.; Schmidt, Scott
Abstract : Background: Prompt diagnosis of breast implant infection is critical to reducing morbidity. A high incidence of false-negative microbial culture mandates superior testing modalities. Alpha defensin-1 (AD-1), an infection biomarker, has outperformed culture in diagnosing periprosthetic joint infection with sensitivity/specificity of 97%. After previously demonstrating its feasibility in breast implant-related infection (BIRI), this case-control study compares the accuracy of AD-1 to microbial culture in suspected BIRI. Methods: An institutional review board–approved, prospective, multicenter study was conducted of adults with prior breast implant reconstruction undergoing surgery for suspected infection (cases) or prosthetic exchange/revision (controls). Demographics, perioperative characteristics, antibiotic exposure, and implant pocket fluid were collected. Fluid samples underwent microbial culture, AD-1 assay, and adjunctive markers (C-reactive protein, lactate, cell differential); diagnostic performance was assessed by means of sensitivity, specificity, and accuracy from receiver operating characteristic curve analysis, with values of P < 0.05 considered significant. Results: Fifty-three implant pocket samples were included (cases, n = 20; controls, n = 33). All 20 patients with suspected BIRI exhibited cellulitis, 65% had abnormal drainage, and 55% were febrile. All suspected BIRIs were AD-1 positive (sensitivity, 100%). Microbial culture failed to grow any microorganisms in four BIRIs (sensitivity, 80%; P = 0.046); Gram stain was least accurate (sensitivity, 25%; P < 0.001). All tests demonstrated 100% specificity. Receiver operating characteristic curve analyses yielded the following areas under the curve: AD-1, 1.0; microbial culture, 0.90 ( P = 0.029); and Gram stain, 0.62 ( P < 0.001). Adjunctive markers were significantly higher among infections versus controls ( P < 0.001). Conclusions: Study findings confirm the accuracy of AD-1 in diagnosing BIRI and indicate superiority to microbial culture. Although further study is warranted, AD-1 may facilitate perioperative decision-making in BIRI management in a resource-efficient manner. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, II.